IASA Stands with Ukraine - Editors, RIAS (Review of International American Studies, 2022)
As a world-wide community of compassionate humans, the International American Studies Association unequivocally condemns the Russian Federation’s barbaric invasion of sovereign Ukraine. Calling upon the Governments of all peace-loving nations to work together towards the immediate cessation of hostilities, we simultaneously encourage all IASA members to donate a fraction of their incomes to the organizations saving lives in the fighting Ukraine or helping the Ukrainian refugees throughout Eastern Europe and world wide. Preferring action to empty verbiage, we therefore ask all of the compassionate human beings to consult the list below. Based on the U.S. news guideline on “How to Help Ukraine,” the list collects organizations and institutions that will appreciate every penny we can spare. IASA stands for peace, and therefore IASA stands with Ukraine. Join IASA.